Investigation on the Needs of Obstetricians & Gynecologists in Different Types of Hospitals for the Content and Forms of Continuing Medical Education and Training - Hanbi Wang; Jie Chen; Zhiyuan Zhang; Han Dong; Ying Zou; Wei Wang; Qingmei Zheng; Ying Feng; Zhangyun Tan; Xiaoqin Zeng; Yinqing Zhao; Yanfang Wang; et al. (Clinical and Experimental Obstetrics & Gynecology)
Background: Medicine is to some extent an empirical science that requires repeated clinical practice. To explore the needs of obstetricians & gynecologists (Ob & Gy) in different kinds of hospitals for continuing medical education (CME) training content and forms. Method: From April 2020 to May 2020, an online questionnaire was distributed on the largest academic training platform for Ob & Gy in China, which included doctors’ mastery of diseases, training content and forms of CME. Results: A total of 4458 questionnaires were returned, of which 3954 were included in the study. There is a significant statistical difference between doctors in general hospitals, maternity specialized hospitals, or maternity and child specialized hospitals in the mastery of most common gynecological and obstetric diseases, among which, doctors in general hospitals have a better mastery (p < 0.001). Generally, doctors in different types of hospitals have a lower mastery of gynecological endocrine-related diseases; doctors in general hospitals have a better mastery of abnormal uterine bleeding (Exp 1.25, 95% Confidence Interval (CI) 1.09~1.44, p = 0.00), and doctors in specialized hospitals are better at infertility and precocious puberty/delayed pubertal development (p = 0.00). The preferred professional direction and training for doctors in different types of hospitals were to strengthen the knowledge of gynecological endocrine diseases through online teaching. Conclusions: Doctors in different types of hospitals generally have lower mastery of gynecological endocrine-related diseases, and doctors in general hospitals have a better mastery of common gynecological and obstetric diseases than those in specialized hospitals. The training content with the greatest need focuses on common gynecological endocrine-related diseases. Online teaching is the most popular educational model.